Hubungan Humor, Kecerdasan Emosi, dan Tipe Kepribadian (OCEAN) pada Remaja - Erik Wijaya (Fakultas Psikologi Universitas Tarumanagara, 2020)
This study examines the relationship between humor, emotional intelligence and personality types. Based on the limitations of various studies on humor it is important to agree with intelligence as well as the type of ownership they have. This is because considering subjects who have certain personality types will choose a different style of humor. Personality in this case is OCEAN consists of five type, those are openness, conscientiousness, extraversion, agreeableness dan neuroticism. Humor consist of three types, those are cognitive humor, neutral humor, and violence humor. Likewise, emotional intelligence possessed by individuals will determine how each of them use humor in everyday life. Youth research subjects from several schools and universities. The sampling method uses convenience sampling technique. Respondent in this research is 1000, consist of male 425 subject (42,5%) and female 575 subject (57.5%). This research produces findings that show a significant relationship between variables and the greatest value in agreeableness personality with emotional intelligence in r = 0.265, p = 0.000 <0.05. The next significant relationship is cognitive humor with emotional intelligence in r = 0.083, p = 0.009 <0.05. The last significant relationship is neutral humor with consciousness personality in r = 0.119, p = 0.000 < 0.05.